Creative Economy Analysis with Penta Helix Identification in Tanjung Bumi Blue Coast Culinary MSMES Bangkalan Regency - Dimas Mahmudi Umar; Alvin Sugeng Prasetyo (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
One of the things that will have a positive impact on the economy of Bangkalan Regency is the growth of the creative economy. This system relies on human creativity and ideas to drive economic activities. The creative economy emphasizes the creation of diverse creative thoughts and ideas as the main source of inspiration in the economic movement. The government is currently concentrating on the growth of the creative economy in the hope of helping MSMEs in Bangkalan Regency, especially the Tanjung Bumi Blue Beach tourist attraction, develop faster. The purpose of this study is to design a creative economy plan for the culinary subsector in the Tanjung Bumi Biru Beach tourist area, Bangkalan Regency. SWOT and Penta Helix techniques were used in the methodology of this study. Where the strategy is intended to boost Tanjung Bumi blue beach tourism and culinary MSME income. The increase in revenue is due to more and more visitors taking full advantage of digital tourism.